Efficiency and convergence in the Jamaican banking sector 1998 - 2007 - Jenifer Daley; Kent Matthews (Cardiff University, Cardiff Business School, 2009)
Deregulation, re-regulation and continuing globalisation embody an imperative that banks increase efficiency to survive. We employ non-parametric bootstrap DEA to measure technical efficiency among Jamaican banks between 1998 and 2007. In addition, we test for conditional convergence to identify pointing variables for technical efficiency. Overall, the results suggest that there has been a tendency towards improvement in bank efficiency levels for the largest banks. The findings show strong evidence of conditional convergence, which means that each bank is converging to its own steady-state and that GDP growth, ownership and size are the major influences on levels of technical efficiency.
Keywords: G21; G28; 330; Bank efficiency; DEA; Bootstrap; Convergence; Jamaica; Bank; Unternehmenserfolg; Produktivität; Jamaika